Media and Communication: Why Another Journal? - Bradley S. Greenberg; Hannes Haas; Elisabeth Klaus (Media and Communication, 2013)
Indeed, there are some three dozen English-language journals now that deal with one or another or multiple aspects of the field of media and (mass) communication. Would another journal not be redundant? We think not. Media and Communication, henceforth shortened to MaC, will possess a specific combination of attributes that are not replicated elsewhere and together result in the unique position of the journal.